Analytical Study of Self-Defence Techniques as a Preventive Measure against Workplace Harassment among Women in Delhi - Pradhan, Sangeeta; Yadav, Sunita (Journal of Neonatal Surgery, 2025)
Workplace harassment continues to pose a significant challenge to the safety, dignity, and professional well-being of women, particularly in metropolitan cities such as Delhi where diverse organisational structures and socio-cultural complexities prevail. Although legislative measures and organisational policies have been introduced to address workplace harassment, preventive strategies that empower women at the individual level remain underexplored. This study analytically examines the role of self-defence techniques as a preventive measure against workplace harassment among women in Delhi. Using a quantitative research design, primary data were collected from women employees across multiple sectors to assess key dimensions including self-defence techniques, harassment incidents, confidence and preparedness, fear and vulnerability, safety awareness, and organisational safety climate. The study employs rigorous statistical techniques, including reliability analysis, exploratory factor analysis, and Partial Least Squares–Structural Equation Modelling, to ensure the validity and robustness of the findings. The results indicate that self-defence techniques are positively associated with enhanced confidence, preparedness, and safety awareness, while contributing to a reduction in perceived fear and vulnerability among women employees. Furthermore, the findings highlight the moderating role of organisational safety climate in strengthening the preventive impact of self-defence practices.